Split Ticket Voting in the 2019 Simultaneous Presidential and Legislative Elections in West Sumatra - Pangi Syarwi; Ramlan Surbakti; Muhammad Asfar (Publikasi Indonesia, 2025)
This study analyzes the phenomenon of split ticket voting in the 2019 Simultaneous Elections in West Sumatra. The method used is a quantitative approach with primary data sources in the form of a survey of people's socio-political preferences, as well as secondary data from academic literature. The dependent variables in this study were split ticket voting, while the independent variables included party-ID, candidate personalization, and identity politics polarization. The results of the analysis show that these three variables significantly affect the tendency of voters to divide their choices between legislative candidates and presidential candidates. The findings also show that high levels of ideological identification tend to lower the likelihood of split ticket voting, while weak ideological ties to political parties reinforce this phenomenon. Therefore, this research confirms the importance of parties maintaining their ideological foundations to strengthen voter loyalty and reduce fragmented electoral behavior.